Effect of the mass of the ball on the kinematics of the handball throw - Marcos Gutiérrez-Dávila; Francisco Sanchez-Sanchez; Alberto Gutiérrez-Castro; Carmen Gutiérrez Cruz (E-balonmano.com: Revista de Ciencias del Deporte, 2022)
The aim of this study was to discriminate the effect of five increases of 15% in the mass of the ball on the most significant kinematic variables that determine the throwing performance. The sample was comprised of twelve male players specializing in front-line throws and belonging to the Spanish Asobal Handball League. Every throw was recorded by two video cameras temporally synchronized at 250 Hz, which allowed us to obtain the spatial coordinates of a model made up of five body markers and the geometric center of the ball. From these coordinates, the components of the positions and linear velocity of the ball were determined, in addiction, the angular positions and velocities of vertical rotation of the upper trunk, shoulder flexion, external / internal rotation of the shoulder, and flexion / extension of the elbow were also obtained. The results indicate that the velocity of the ball decreases with the increase in the mass of the ball and the angular velocity of internal rotation of the shoulder is the most affected factor, followed by the extension of the elbow. The throwing time increases when the mass of the ball increases due to the longer backward movement time of the ball. It is estimated that a 15% increase in the ball mass has no effect on the kinematics of the throw.